JORDAN LEFT DERIVATIONS AND GENERALIZEDJORDAN LEFT DERIVATIONS ON RINGS - Majeed, A.; Shaheen, Rajaa (Iraqi Journal of Science, 2025)
In this paper we have studied Jordan left derivation of a ٢-torsion free ring whichhas a commutator left non- zero divisor and we initiate the study of generalizedJordan left derivation of a ٢-torsion free ring, which has a commutator left non- zerodivisor.